2009
DOI: 10.1136/jnnp.2008.162594
|View full text |Cite
|
Sign up to set email alerts
|

Risk of arrhythmia in type I myotonic dystrophy: the role of clinical and genetic variables

Abstract: Male sex, age and muscular disability were strongly associated with the development of arrhythmia in DM1. However, all of these variables were weak predictors of arrhythmic risk. These results suggest that other factors may be involved in the development of cardiac conduction abnormalities in DM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…In 2 (n = 419) of 6 studies a significant positive correlation was found between CTG repeat length and conduction abnormalities [20,24]. One study (n = 245) found a positive non-significant correlation between CTG repeat length and conduction abnormalities [9], whereas three smaller studies (in total n = 183) found no correlation between CTG repeat length and conduction abnormalities [12,17,18] (Table 3). Five (n = 770) of eight studies elaborated on the correlation between CTG repeat length and arrhythmic events (supraventricular and ventricular arrhythmias).…”
Section: Ctg Repeat Length and Cardiac Involvementmentioning
confidence: 93%
See 4 more Smart Citations
“…In 2 (n = 419) of 6 studies a significant positive correlation was found between CTG repeat length and conduction abnormalities [20,24]. One study (n = 245) found a positive non-significant correlation between CTG repeat length and conduction abnormalities [9], whereas three smaller studies (in total n = 183) found no correlation between CTG repeat length and conduction abnormalities [12,17,18] (Table 3). Five (n = 770) of eight studies elaborated on the correlation between CTG repeat length and arrhythmic events (supraventricular and ventricular arrhythmias).…”
Section: Ctg Repeat Length and Cardiac Involvementmentioning
confidence: 93%
“…In 3 (n = 365) of 7 studies, there was a significant positive correlation between the severity of muscular involvement and conduction system impairment [9,13,18]. One study (n = 406) found a non-significant positive association between severity of muscular impairment and conduction abnormalities.…”
Section: Neuromuscular Affection and Cardiac Involvementmentioning
confidence: 97%
See 3 more Smart Citations